The Milan system for reporting salivary gland cytopathology: A study of inter‐observer reproducibility. Issue 8 (9th May 2019) - Layfield, Lester J.; Esebua, Magda; Yang, Zhongbo; Vatzmitsel, Maryna; Giorgadze, Tamara; Schmidt, Robert
Abstract: Background: In 2018, the Milan System for Reporting Salivary Gland Cytopathology was published defining a diagnostic categorization scheme with known malignancy risks and clinical follow up recommendations. Inter‐observer reproducibility of the categories was not defined. Methods: Salivary gland fine‐needle aspirations (FNA) were reviewed over a 5 year period and classified by three independent observers. Inter‐observer reproducibility was estimated using observed agreement and chance corrected agreement (Cohen's kappa). Results: Four hundred and eight cases were reviewed with chance corrected agreement of 0.42 for the original Milan System and 0.48 for a modified system using "similar follow up" categories. Categories 4A and 6B showed substantial agreement (kappa =0.71 and 0.72). Conclusion: The Milan System shows moderate over all agreement between observers. Strongest inter‐observer agreement was seen for categories 4A and 6B.